Fifty Years After Bretton Woods : The Future of the IMF and the World Bank: Proceedings of a Conference held in Madrid, Spain, September 29-30, 1994. (Washington, D.C. : International Monetary Fund, 1995)
This volume, edited by James M. Boughton and K. Sarwar Lateef, contains the proceedings of a conference held in Madrid, Spain, in 1994, by the IMF and the World Bank to commemorate the fiftieth anniversary of the Bretton Woods conference of July 1944 that created the two institutions. The conference provided a forum for reflection and for reassessing the roles of the institutions as they approach the twenty-first century.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet